Emery's elements of medical genetics - Mueller, Robert F; Young, Ian D (Churchill Livingstone, 2001)
(Churchill Livingstone) St. James\'s Hospital, Leeds, UK. Textbook for medical students. Features basic science and clinical practice, photographs showing examples of genetic disorders, boxes summarizing key points of chapters, and more. Previous edition: c1998. Softcover.
Keywords: lékařská genetika; Genetics, Medical; genetika, lékařská genetika